Case study: Industry-sponsored mechanical engineering capstone senior design program. Issue 4 (October 2019) - Abu-Mulaweh, Hosni I; Abu-Mulaweh, Nusaybah A
In the mechanical engineering program at Purdue University Fort Wayne, capstone senior design projects are accomplished during an undergraduate's senior year and span two semesters. In the first semester, the formulation of the problem statement occurs and basic conceptual designs are generated and evaluated. After evaluation, the best design that satisfies the requirements is selected, and a complete detailed design is obtained by the end of the first semester. In the second semester, a prototype of the finished design is built, tested, and evaluated. Over the years, partnerships with local industry have been formed to provide students with real-world projects for senior design. The aim of this paper is to present how industry partnerships have been developed, discuss the degree of involvement and the role of industry-sponsors in the course of the design project, and briefly describe the industry-sponsored design projects that were completed in the 2016/2017 academic year.